Primary Fascial Closure During Laparoscopic Ventral Hernia Repair Improves Patient Quality of Life: A Multicenter, Blinded Randomized Controlled Trial. Issue 3 (March 2020) - Bernardi, Karla; Olavarria, Oscar A.; Holihan, Julie L.; Kao, Lillian S.; Ko, Tien C.; Roth, John S.; Tsuda, Shawn; Vaziri, Khashayar; Liang, Mike K.
Abstract : Background: Observational studies have reported conflicting results with primary fascial closure (PFC) versus bridged repair during laparoscopic ventral hernia repair (LVHR). Objective: The aim of the study was to determine whether when evaluated in a randomized controlled trial (RCT), PFC compared to bridged repair would improve patient quality of life (QoL). Methods: In this blinded, multicenter RCT, patients scheduled for elective LVHR (hernia defects 3 to 10 cm on computed tomography scan) were randomized to PFC versus bridged repair. Primary outcome was change in QoL after LVHR using a validated, hernia-specific survey (1 = poor QoL and 100 = perfect QoL) that measures pain, function, cosmesis, and satisfaction. Secondary outcomes were postoperative surgical site occurrences (including hematoma, seroma, surgical site infection, and wound dehiscence), abdominal eventration, and hernia recurrence. The trial was powered to detect a difference in change in QoL of 7 points between the study groups. Outcomes were compared with Mann-Whitney U test or chi-square. Results: A total of 129 patients underwent LVHR and 107 (83%) completed follow-up at 2 years. Patients from both groups were similar at baseline. On median follow-up of 24 months (range: 9–42), patients treated with LVHR-PFC had on average a 12-point higher improvement in QoL compared to bridged repair (improvement in QoL, 41.3 ± 31.5 vs 29.7 ± 28.7, P value = 0.047). There were no differences in surgical site occurrence, eventration, or hernia recurrence between groups. Conclusions: Among patients undergoing elective LVHR, the fascial defect should be closed. This is the first RCT demonstrating that PFC with LVHR significantly improves patient QoL. Trial Registration: This trial was registered with clinicaltrials.gov (NCT02363790) Abstract : Supplemental Digital Content is available in the text